Relationships between land cover, riparian vegetation, stream characteristics, and aquatic insects in cloud forest streams, Mexico - Astudillo, Manuel R; Novelo-Gutiérrez, Rodolfo; Vázquez, Gabriela; García-Franco, José G; Ramírez, Alonso (Hydrobiologia, 2016)
Cloud forest streams are diverse ecosystems that provide valuable services (i.e., drinking water), but are threatened by anthropogenic activities on the watershed. We assessed the relationships between forest cover in the catchment, riparian vegetation, water chemistry, channel geomorphology, and the diversity of aquatic insects (taxonomic and functional diversity) in streams running through cloud forest in the upper part of La Antigua watershed, Mexico. Variables and aquatic insect assemblages were sampled during the dry and rainy seasons, in six streams draining different land covers, including forest, pasture, and agriculture. Aquatic insect assemblages were related to forest cover and riparian vegetation, as well as to various physical and chemical parameters of streams. Certain insect genera (Suragina and Anacroneuria) were indicators of little forest cover and forested streams, respectively. Functional Feeding Groups were related to physical and chemical parameters. Seasonality was also found to influence both the physical and chemical characteristics of streams and insect assemblages. Our findings reveal that cloud forest streams in La Antigua watershed are diverse and their insect assemblages are affected by land cover both in the watershed and the riparian zone, and by the associated changes in the stream physical and chemical characteristics.